Sejarah Perkembangan Pendidikan Islam di Malaysia dari Pondok ke Sekolah Agama Modern - Eva Fitriyani; Mikaila Nur Tsaqifa Al Maarif; Naila Rahma Aulia (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines the historical development of education in Malaysia, which has undergone a shift from the traditional pondok system to modern religious schools. This change was influenced by various factors, including social dynamics, colonial influence, and societal demands for a more structured and relevant education system. This study aims to explain this development process and identify the various factors driving this change. The research employed a qualitative approach through literature review, utilizing various sources, books, journals, and scientific documents, which were analyzed descriptively to gain a deeper understanding. The results show that the pondok system, which was initially informal and simple, even focusing only on teaching religious knowledge and moral development, underwent changes due to the influence of colonialism, the development of Western education, and the increasing societal need for formal education. This change gave rise to modern madrasahs and religious schools with more structured curricula, integrating religious and general knowledge, and implementing more systematic methods. The findings of this study confirm that this development did not completely eliminate the pondok system, but rather developed it into a more comprehensive educational system, enabling Islamic education in Malaysia to remain steadfast in Islamic values ​​and adapt to modern demands.